Introduction to Food Engineering - Singh, .Paul (Academic Press, 2014)
Long recognized as the bestselling textbook for teaching food engineering to food science students, this 5e transitions with today’s students from traditional textbook learning to integrated presentation of the key concepts of food engineering. Using carefully selected examples, Singh and Heldman demonstrate the relationship of engineering to the chemistry, microbiology, nutrition and processing of foods in a uniquely practical blend. This approach facilitates comprehensive learning that has proven valuable beyond the classroom as a lifetime professional reference.